(untitled) (Journal of Media studies, 2023)
This article proposes a method for assessing the effects of fiscaldecentralization on economic development. The relationship between the properlevel of fiscal decentralization and economic growth for 17 regions and cities ofrepublican significance in Kazakhstan from 2010 to 2020 was evaluated usingpanel data. Panel cointegration and dynamic ordinary least squares (DOLS)results suggest that fiscal decentralization has a negative and significant impacton gross regional product. The study found that both income and expendituredecentralization have a negative impact on economic growth, and that furtherfiscal decentralization currently has a negative impact on gross regional product(GRP) growth. Given the premise that fiscal decentralization usually promoteslocal economic progress, this consistently significant and powerful result of ourempirical analysis is surprising.